A tetrahedron from homooxacalix[3]arene, the fifth Platonic polyhedron from calixarenes and uranyl - Wu, Jin-Cheng; Escudero-Adán, Eduardo C.; Martínez-Belmonte, Marta; de Mendoza, Javier (Frontiers in Chemistry, 2023)
A self-assembled tetrahedral cage results from two C3-symmetry building blocks, namely homooxacalix[3]arene tricarboxylate and uranyl cation, as demonstrated by X-ray crystallography. In the cage, four metals coordinate at the lower rim with the phenolic and ether oxygen atoms to shape the macrocycle with appropriate dihedral angles for tetrahedron formation, whereas four additional uranyl cations further coordinate to the upper-rim carboxylates to finalize the assembly. Counterions dictate the filling and porosity of the aggregates. Whereas potassium induces highly porous structures, tetrabutylammonium yields compact, densely packed frameworks. The tetrahedron metallo-cage complements our previous report (Pasquale et al., 2012) on uranyl organic frameworks (UOF’s) from calix[4]arene and calix[5]arene carboxylates (octahedral/cubic and icosahedral/dodecahedral giant cages, respectively), and completes the assembly of all five Platonic solids from just two chemical components.